(Thio)urea-catalyzed Friedel-Crafts Reaction: Synthesis of Bis(indolyl)-methanes - Rivas-Loaiza, Juan A.; Reyes-Escobedo, Carlos E.; Lopez, Yliana; Rojas-Lima, Susana; García-Merinos, Juan P.; López-Ruiz, Heraclio (Letters in Organic Chemistry, 2019)
Bis(indolyl)methane derivatives (BIMs) were synthesized in moderate to good yields by (thio)urea catalyzed electrophilic substitution of indole (2) with various aldehydes 1. Reactions were performed under conventional and microwave (MW) heating, either using 1,2-dichloroetane as solvent or without solvent. The procedure using microwave heating was also applied to the synthesis of the natural products vibrindole A (3n), arsindoline A (3i), arundine (3o) and tris(1H-indol-3-yl)methane (3j). Additionally, the synthesis of streptindole was carried out via intermediate 3g. This methodology is well suited for the synthesis of bis(indolyl)methanes: it offers good yields of products, low sensitivity to moisture and oxygen, high tolerance to different functional groups on the aldehydes such as alkynes and trimethylsilane, and simplicity in operation
Keywords: Indole